THE POST-GRADUATION SCORTS SENSU IN BRAZIL: A STUDY FROM LEGAL DOCUMENTS - Bueno da Silva, Nathalia Delgado [UNESP]; Brandao, Carlos da Fonseca [UNESP] (Univ Metodista Piracicaba-unimep, 2020)
The present study aims to identify the directions for post-graduation, stricto sensu, in Brazil over the years. This level of education emerged in the country in a regulated manner in the 1960s, and is now guaranteed as a teaching system, with representation and academic status in front of the post-graduate lato sensu. The study is of a bibliographic and documentary nature, based on Opinion n. 977 of December 3, 1965 and the National Graduate Plans (PNPG), which in a directive way interfered so that this level of education was consolidated. The documents reflect the pretensions and needs of the era in which they encompass, being articulated to the social, political and economic context. This reflection can be verified because there is linearity in the postgraduate in certain cycles, as its legal initiation and the need to establish formal guidelines to unify the programs; later, the intentions to measure the quality of the expansion, and thus, the maintenance of a System, that today is the subject of several discussions, whether about its evaluation, or about its organization and conjuncture.
Keywords: POSTGRADUATE STRICTO SENSU; NATIONAL GRADUATE PLAN (PNPG); EDUCATIONAL PUBLIC POLICIES